Clinical monitoring of steatorrhoea in cystic fibrosis. Issue 1 (January 1990) - Walters, M P; Kelleher, J; Gilbert, J; Littlewood, J M
Abstract : In 100 patients with cystic fibrosis the severity of steatorrhoea was assessed by three separate methods. Using chemical faecal fat assay as the gold standard, two other rapid and inexpensive methods were compared with it. The steatocrit method proved unreliable in our hands and gave little indication of the presence or severity of steatorrhoea. The more simple microscopy method was highly sensitive (97%) and only three of 80 patients with steatorrhoea were missed. All patients with severe steatorrhoea (greater than 60 mmol fat/day) were clearly demonstrated. The method is applicable to spot faecal samples and can readily be carried out on an outpatient basis. In centres where faecal fat assays are not available, the simple and cheap microscopic examination will give some indication of the response to enzyme treatment and may also help to identify non-compliant individuals.